2009
DOI: 10.1007/s10804-009-9071-1
|View full text |Cite
|
Sign up to set email alerts
|

The Meanings and Manifestations of Religion and Spirituality among Lesbian, Gay, Bisexual, and Transgender Adults

Abstract: The present study employed a mixed method approach in the effort to explore religious and spiritual practices among lesbian, gay, bisexual, and transgender (LGBT) individuals, as well as the meanings ascribed to the terms religiosity and spirituality by LGBT adults. Data were collected via a cross-sectional survey consisting of open-and close-ended items among 498 LGBT (lesbian, gay, bisexual, transgender) identified individuals attending an annual Pride event in a large northeastern city. Both quantitative an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
113
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 110 publications
(121 citation statements)
references
References 37 publications
6
113
0
2
Order By: Relevance
“…In particular, existential well-being seemed to be more positively rated than religious well-being. These findings are consistent to the ones found by other authors in different contexts, such as Ridge et al (2008) and Halkitis et al (2009), and highlight that spirituality plays an important role in the lives of many LGB people.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…In particular, existential well-being seemed to be more positively rated than religious well-being. These findings are consistent to the ones found by other authors in different contexts, such as Ridge et al (2008) and Halkitis et al (2009), and highlight that spirituality plays an important role in the lives of many LGB people.…”
Section: Discussionsupporting
confidence: 92%
“…shown that younger people may struggle more with the rejection from their churches (Garcia et al, 2008) and that older LGB persons are more likely to have a faith in a spiritual force (Halkitis et al, 2009;Henrickson, 2007). However, these findings also do speak to the resilient nature of older LGB persons in Portugal, in that only recently have LGB issues been openly and constructively discussed in society.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations